1851 R.I. Pub. Laws 204 - (:unkn) unknown (My University, 1851)
Ch. 80, § 2 (Jan. Sess. 1857): Banned shooting galleries (or any building or enclosure) where firearms are used for practicing firing ball or shot from the "compact part of the town of Newport"; authorized the town to collect a tax on shooting galleries.
Keywords: SHOOTING RANGES OR GALLERIES